Gender mainstreaming as institutional innovation? Gender budgeting, velvet triangles, and (good) practices (2014)
Abstract: This article is concerned with the understanding of gender mainstreaming as an institutional innovation, examining the case of gender budgeting. It begins, in section one, by identifying themes in existing gender mainstreaming literature, and then in section two considering the potential of gender budgeting to tackle institutional innovation in Australia and Great Britain. Underlying both sections are questions about the subjects involved in the implementation of gender mainstreaming strategies. In order to answer to those questions, the last section deals with the concept of velvet triangle as analytic lens to understand how strategic alliances among actors might result in gender sensitive public policy.